Penerapan Pemberlakuan Pembatasan Kegiatan Masyarakat (PPKM) dan Bangun Rumah Singgah di Dalapuli Bolaang Mongondow Utara - Munirah, Munirah; Patilimi, Rasni; Soleman, Febriyanti; Lajulu, Dahlian; Mondo, Siska (Madani: Jurnal Pengabdian Ilmiah, 2021)
This article aims to reveal how the implementation of restrictions on community activities in North Dalapuli Bolaang Mongondow. The method used is qualitative by making direct observations in the field. The results showed that the spread of the Covid-19 virus in Indonesia had a major impact on the Indonesian people, both in the fields of education, health, economy, socio-culture and others, especially in Dalapuli village, North Bolaang Mongondow Regency which had an impact on the surrounding community with the implementation of PPKM. (implementation of restrictions on community activities). With the implementation of this PPKM all community activities are limited due to the spread of COVID-19. In the implementation of PPKM, the village government and KKS-DR students prepare plans for the implementation, starting from determining the location, collecting data, presenting data, planning, implementing and drawing conclusions. The results of this plan indicate that the positive response of the community to the implementation of PPKM is considered important that awareness of the spread of covid-19 and maintaining body resistance, also cleaning the surrounding environment and using masks when leaving the house.